Effects of Socio-Economic Conditions on the Relationship between Public and Private investments in the CEMAC Zone - Ngouhouo, Ibrahim; Nguekam, Orfé Chouafi; Armand, Gilbert Noula; Oumbe, Honoré Tekam (Asian Journal of Economic Modelling, 2019)
This study aims at examining the effects of socio-economic conditions on the relationship between public investments and the productivity of the private sector in CEMAC countries between 1982 and 2016. Theoretical and empirical studies on this issue yield different results depending on the period and countries considered. After estimating an ARDL (Autoregressive Distributed Lag) model, we find that there exists a positive effect in the short and long run of public investment on private sector investments only in Congo, Gabon, the Central African Republic and Chad. We also find that in the short run, unlike in Cameroon, Equatorial Guinea, Chad and the Central African Republic where the socio-economic conditions reduce the level of public investments, they rather reinforce their contribution to private sector investment in Gabon and Congo. In the long run, they however improve the efficiency of public investments in Cameroon and Congo and reduce it in the Central African Republic. There is therefore a need to improve the quality of institutions in order to enable the development of the private sector.